Knowledge, Perceptions, and Practices in Cervical Cancer Screening Among Female Nurses and Midwives - Paripurna, Yoga; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Background: Cervical cancer is the fourth most common cancer among women worldwide, with persistent high-risk human papillomavirus (HPV) infection (types 16 and 18) accounting for approximately 70% of cases. Despite the availability of HPV vaccination and screening programs, Indonesia has a low screening coverage rate (12%). Female nurses and midwives play a crucial role in cervical cancer prevention, yet their knowledge, perceptions, and screening practices remain underexplored. Objective: This study aims to assess the knowledge, perceptions, and screening practices of female nurses and midwives in Jepara District, Indonesia, and identify key barriers to participation in screening programs. Methods: A descriptive study was conducted at RSUD Dr. Rehatta, Jepara, involving 74 registered female nurses and midwives. Data were collected using a validated self-administered questionnaire, and descriptive analysis was performed using SPSS version 20. Results: The majority of respondents were aged 20–30 years (37.1%) and over 40 years (37.1%), with 87.1% married. While 98.6% were aware of cervical cancer and 89.2% identified HPV as its primary cause, only 35.3% knew the recommended screening frequency. Although 94.7% recognized cervical cancer as preventable, only 40.0% perceived themselves at risk, and merely 32.0% had undergone screening. The primary barriers included fear of diagnosis (74.7%), embarrassment (56.0%), and misconceptions regarding the necessity of screening in the absence of symptoms (54.7%). Conclusion: Despite high awareness of cervical cancer, screening participation remains low due to psychological, social, and cultural barriers. Structured education, mandatory training, and targeted awareness programs are essential to improving screening uptake among healthcare professionals.